Endoscopic CO2 laser surgery for supraglottic cancer : ten years of experience - Bumber, Željko (Array, 2009)
Abstract: We present our experience with primary CO2 laser surgery for planocellular supraglottic carcinoma. During a ten- -year period, we performed 64 curative supraglottic laryngectomies. Twenty-nine patients presented with T1 and 35 with T2 carcinoma. There were 46 patients without regional and/or distant metastases (N0 neck), and 18 patients with N+ neck. Thirty-three (52%) patients were treated with surgery alone, and in 31 (48%) patients surgical procedure was combined with radiotherapy. Estimated overall 5-year survival for all patients was 89%. Local and regional tumor control as well as survival rate were comparable with the results of other therapeutic options, i.e. radiotherapy or open supraglottic laryngectomy. Functional results outline the advantages of endoscopic laser surgery for laryngeal carcinoma. Transoral endoscopic CO2 laser surgery is efficacious treatment for T1 and T2 supraglottic carcinoma, and can be combined with neck dissection and postoperative irradiation